2007
DOI: 10.1002/ccd.21072
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization in severe left ventricular dysfunction: Outcome comparison of drug‐eluting stent implantation versus coronary artery by‐pass grafting

Abstract: In selected high risk patients with severe LV dysfunction revascularization with DES implantation offers comparable long term mortality and MACCE rate to CABG patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 25 publications
1
42
1
2
Order By: Relevance
“…In a subanalysis of secondary end points, we found significantly reduced risk for MI and RR in patients treated with CABG versus PCI. 20,[22][23][24][25]30,33,35 ; (B) repeat revascularization 20,22,23,25,28,33,35 ; and (C) stroke. 20 46 and subsequent metaanalyses 47 have suggested that intermediate-term mortality after interventional revascularization using modern stent systems is comparable to CABG, with a reduced risk of stroke but a higher need for RR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a subanalysis of secondary end points, we found significantly reduced risk for MI and RR in patients treated with CABG versus PCI. 20,[22][23][24][25]30,33,35 ; (B) repeat revascularization 20,22,23,25,28,33,35 ; and (C) stroke. 20 46 and subsequent metaanalyses 47 have suggested that intermediate-term mortality after interventional revascularization using modern stent systems is comparable to CABG, with a reduced risk of stroke but a higher need for RR.…”
Section: Discussionmentioning
confidence: 99%
“…20,22,23,25,28,30,33,35 There was a statistically significant reduction in RR with CABG compared with PCI treatment; the respective rates were 5. …”
Section: Repeat Revascularizationmentioning
confidence: 92%
See 2 more Smart Citations
“…3 Nowadays, with the modern tools and the experience of the surgeons in performing off-pump revascularisation, it is possible to reach all territories of the heart, even with arterial grafts. [4][5][6] In our daily practice we are doing less hybrid coronary interventions and more and more complete total arterial off-pump CABG operations for three-vessel disease. Numbers of distal anastomoses vary from three to six, even in patients with impaired left ventricular function.…”
mentioning
confidence: 99%